Bambara groundnut: an exemplar underutilised legume for resilience under climate change - Mayes, S.; Ho, W.K.; Chai, H.H.; Gao, X.; Kundy, A.C.; Mateva, K.I.; Zahrulakmal, M.; Hahiree, M.K.; Kendabie, P.; Licea, L.C.S.; Massawe, F.; Mabhaudhi, Tafadzwanashe; et al. (Springer, 2019)
World agriculture is currently based on very limited numbers of crops, representing a significant risk to food supplies, particularly in the face of climate change which is expected to increase the frequency of extreme events. Minor and underutilised crops can help to develop a more resilient and nutritionally dense future agriculture. Bambara groundnut [Vigna subterranea (L.) Verdc.[, as a drought resistant, nitrogen-fixing, legume has a role to play. However, as with most underutilised crops, there are significant gaps in knowledge and also negative traits such as ‘hard-to-cook’ and ‘photoperiod sensitivity to pod filling’ associated with the crop which future breeding programmes and processing methods need to tackle, to allow it to make a significant contribution to the well-being of future generations. The current review assesses these factors and also considers what are the next steps towards realising the potential of this crop.